Pengaruh Pembelajaran Berdiferensiasi Terhadap Minat Belajar Siswa Dalam Kurikulum Merdeka - Hartini, Billyun Dianata; Usman, Ali; Prafitasari, Aulya Nanda (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out whether there are differences in interest in learning between students who apply differentiated learning and those who do not. This type of research is quantitative research with a quasi-experimental method. The sample in this study was class X4 as the experimental class and X1 as the control class. Data was collected using an interest questionnaire given to both classes. The results of this research show that there is a difference in the learning interest of students who apply differentiated learning and those who do not with a significant Asymp value (2-tailed) of 0.031 < 0.05.